REACTION KINETICS OF GAS GENERATION IN SELECTED SOURCE ROCKS OF THE WEST SIBERIAN BASIN: IMPLICATIONS FOR THE MASS BALANCE OF EARLY-THERMOGENIC METHANE - Schaefer R.G.; Kolloff A.; Littke R.; Galushkin Y.I. (My University, 1999)
About one third of the actual global recoverable natural gas reserves is accumulated in the West Siberian Basin in several super-giant and mega-giant as well as numerous smaller gas fields. The elucidation of the nature of this gas, its mechanisms of formation and accumulation are still a matter of discussion. For instance, it is still not yet clear whether the enormous dry-gas accumulations in Cenomanian reservoirs are of microbial, `early-thermogenic' or catagenetic/metagenetic origin, or if they represent a mixture of these possible formation mechanisms. The present contribution provides new results on the thermal gas generation properties of selected source rocks of the Cretaceous Pokur Formation in the West Siberian Basin. Eight selected source rock core samples of the Pokur Formation and a recent peat sample of the same area were submitted to open-system programmed-temperature pyrolysis, in order to quantify the formation of individual gas compounds, i.e., methane as well as C2 and C3 hydrocarbons. The rock samples were selected according to geological age and maturity, i.e., from the Aptian, Albian, and Cenomanian, with the most immature samples from the latter. Organic carbon contents comprise the whole range from 3 to more than 60%, the elevated values representing typical lignites. A reaction kinetic model system was applied to the `generation curves' of the gases resulting in activation energy distributions and the corresponding pre-exponential `Arrhenius factors'. The kinetic data were combined with the temperature history of two selected wells of the Urengoy area obtained from basin modelling in order to calculate the gas generation on the geological time-scale. It was found that, even for the low temperatures occurring in the Pokur Formation, `early' gas generation could have taken place to a certain, yet small, degree. Under the assumption of a respective catchment area and the accumulation of this gas in the reservoirs, however, methane quantities are in the order of magnitude of the Urengoy gas accumulation. Thus, `early-thermogenic' methane could, at least partially, contribute to the gas accumulated in the reservoirs.
Keywords: Cretaceous; Cenomanian; Albian; Aptian; Mesozoic::Cretaceous; Mesozoic::Cretaceous::Lower::Albian; Mesozoic::Cretaceous::Upper::Cenomanian; Мезозой::Меловая; Мезозой::Меловая::Нижний::Аптский; Мезозой::Меловая::Нижний::Альбский; Mesozoic::Cretaceous::Lower::Aptian; Мезозой::Меловая::Верхний::Сеноманский